2021
DOI: 10.1080/24740527.2020.1858709
|View full text |Cite
|
Sign up to set email alerts
|

Youth and parent perceptions on participating in specialized multidisciplinary pain rehabilitation options: A qualitative timeline effect analysis

Abstract: Background : Little is known about how the specialized treatment journey is perceived by youth with pain-related disability and their parents. Aims : Describe and compare the treatment effects and outcomes as perceived by youth and their parents enrolled in intensive interdisciplinary pain treatment (IIPT) or multimodal treatment (MMT). Methods : Eleven IIPT youth and five parents and three MMT youth and five parents were recruited. All were asked to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Contrary to positive turning points, negative turning points are yet to be discussed in the literature. Only recently the unexplored detrimental effects of multidisciplinary treatment were established through a similar timeline methodology [ 37 ]. When exploring the literature more widely, the negative turning points, as drawn by youths and shown in Figure 3 , resembled the Kubler-Ross Change Curve [ 38 ] that was expanded to describe the response to loss [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to positive turning points, negative turning points are yet to be discussed in the literature. Only recently the unexplored detrimental effects of multidisciplinary treatment were established through a similar timeline methodology [ 37 ]. When exploring the literature more widely, the negative turning points, as drawn by youths and shown in Figure 3 , resembled the Kubler-Ross Change Curve [ 38 ] that was expanded to describe the response to loss [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given adolescents’ increasing independence and cognitive capacity, playing a more active role in treatment, as well as being given voice and space to share, construct, and reconstruct their experience of pain, is developmentally appropriate and in line with treatment benefits identified by youth with chronic pain. 49 Second, providing a more in-depth rationale for the importance of pain memories before the surgery and/or including the elements of intervention throughout the surgery preparation period would allow youth to better understand and get more invested in the intervention. Third, according to the patient partner, the intervention could be improved by explicitly validating and supporting youth during reminiscing.…”
Section: Discussionmentioning
confidence: 99%
“…To improve compatibility and consistency, careful consideration should be given to the need for qualitative and quantitative assessment approaches, ensuring effects adequately capture what is relevant to youth suffering from chronic pain and their parents, while being interpretable to clinicians and funders. A series of recently published studies by our team, which used targeted designs, carefully selected patient‐reported outcome instruments and novel qualitative methods, all influenced by stakeholder input, provide some initial guidance in addressing these gaps 85,89‐92 …”
Section: Discussionmentioning
confidence: 99%
“…A series of recently published studies by our team, which used targeted designs, carefully selected patient-reported outcome instruments and novel qualitative methods, all influenced by stakeholder input, provide some initial guidance in addressing these gaps. 85,[89][90][91][92] This review has many strengths. First, the engagement of various stakeholders, including youth with chronic pain who participated in pediatric-specialized outpatient pain rehabilitation, with skills in conducting knowledge syntheses, added novelty to this knowledge synthesis.…”
Section: Discussionmentioning
confidence: 99%